2022
DOI: 10.1039/d2nr01998a
|View full text |Cite
|
Sign up to set email alerts
|

Dual photothermal nanocomposites for drug-resistant infectious wound management

Abstract: Management of antibiotic-resistant bacteria-induced skin infections for rapid healing remains a critical clinical challenge. Photothermal therapy, which uses mediated hyperthermia to combat such problems has recently been recognised as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…For a wound healing dressing, it has certain antibacterial and even bactericidal properties to significantly reduce the chance of infection on the wound surface and promote the healing of the wound, especially the infected wound ( Liu et al, 2022a ; Li et al, 2022c ; Yu et al, 2022 ). Traditional wound care methods for infected wounds usually use antibiotics to solve the problem of wound infection, but a wide variety of bacterial species and complex environment on the wound surface make it difficult for a single antibiotic to cover all bacterial species, and long-term use of broad-spectrum antibiotics is easy to lead to the colonization and growth of multi-drug-resistant bacteria such as MRSA, further increasing the difficulty of wound healing ( Deurenberg and Stobberingh, 2008 ; Li et al, 2022c ). MXene has a lamellar structure similar to graphene and more abundant surface groups, so the researchers hypothesized that MXene should also have some antibacterial properties.…”
Section: Application Of Mxene and Its Modified Materials In Skin Woun...mentioning
confidence: 99%
“…For a wound healing dressing, it has certain antibacterial and even bactericidal properties to significantly reduce the chance of infection on the wound surface and promote the healing of the wound, especially the infected wound ( Liu et al, 2022a ; Li et al, 2022c ; Yu et al, 2022 ). Traditional wound care methods for infected wounds usually use antibiotics to solve the problem of wound infection, but a wide variety of bacterial species and complex environment on the wound surface make it difficult for a single antibiotic to cover all bacterial species, and long-term use of broad-spectrum antibiotics is easy to lead to the colonization and growth of multi-drug-resistant bacteria such as MRSA, further increasing the difficulty of wound healing ( Deurenberg and Stobberingh, 2008 ; Li et al, 2022c ). MXene has a lamellar structure similar to graphene and more abundant surface groups, so the researchers hypothesized that MXene should also have some antibacterial properties.…”
Section: Application Of Mxene and Its Modified Materials In Skin Woun...mentioning
confidence: 99%
“…BNC applications are vast (Lokhande et al, 2022;Rai and Dhar, 2022), but the combination of BNC with PDA has been less studied. The highly attractive properties of PDA considering its biocompatibility, biodegradability, and high photothermal conversion efficiency makes PDA-BNC membranes very useful to develop photothermal materials, for water treatment, and for wound healing by having antibacterial properties (Jiang et al, 2017;Jun et al, 2019;Li et al, 2022;Wahid et al, 2021).…”
Section: Preparation Of Pda-bncmentioning
confidence: 99%
“…Indeed, the in vitro and in vivo antibacterial efficacy of these nanocomposites was evaluated against S. aureus , E. coli , and MRSA. The results revealed an antibacterial efficacy of 99% under NIR irradiation at 808 nm (1.0 W/cm 2 ), an anti-inflammatory effect, and the regeneration of damaged tissue with a good biocompatibility evaluated by >85% of survival cells [ 57 ]. In another study, the photothermal efficiency of polydopamine nanoparticles was demonstrated in a construct of a gold nanostar/hollow polydopamine Janus nanostructure (GNS/HPDA JNPs).…”
Section: Ptt Combined With Metal or Metal Oxide Nanoparticles As Anti...mentioning
confidence: 99%